2021
DOI: 10.56093/ijans.v91i11.118143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heritability estimates of first lactation fertility traits in Mehsana buffaloes

Abstract: First lactation records of 3068 Mehsana buffaloes sired by 118 sires, under field progeny testing programme distributed in different 149 villages of 14 talukas maintained at Dudhsagar Research and Development Association, Dudhsagar Dairy, Mehsana over a period of 24 years (1989-2012) were used to estimate least squares means and heritability of fertility traits like, first service period (FSP), first calving interval (FCI) and daughter pregnancy rate (DPR). The least squares means of these traits were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
(8 reference statements)
3
2
0
Order By: Relevance
“…The range of calving interval varied significantly across different groups for each factor (Table 3 and Figure 3). In concordance with the present study, Parmar et al (2017) [7] and Purohit et al (2021) [11] reported a significant effect of the AFC group on the calving interval in Mehsana. The findings of this study underscore the importance of non-genetic factors in influencing the fertility of Mehsana buffaloes.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The range of calving interval varied significantly across different groups for each factor (Table 3 and Figure 3). In concordance with the present study, Parmar et al (2017) [7] and Purohit et al (2021) [11] reported a significant effect of the AFC group on the calving interval in Mehsana. The findings of this study underscore the importance of non-genetic factors in influencing the fertility of Mehsana buffaloes.…”
Section: Resultssupporting
confidence: 92%
“…It is depicted in Figure 2 that the overall calving interval has shown declining trends in the last few years indicating that female fertility is also taken care of. Similar significant effects of the period of calving were also observed by Purohit et al (2021) [11] , Parmar et al (2017) [7] , and Galsar et al (2016) [5] in the same breed. This variation may be attributed to the selection and breeding over the years, facilitated by progeny testing programs.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations